Pengembangan Buku Ajar Layanan Prima dengan Pendekatan Search, Solve, Create, Share (SSCS) untuk Memberdayakan Kemampuan Berpikir Kritis Mahasiswa - Veni Rafida (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to develop a prima service textbook based on the Search, Solve, Create, and Share (SSCS) model to empower students' critical thinking skills. The research uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research instruments consist of needs analysis, validation sheets of material experts, design experts, and linguists, student response questionnaires, and pretest and posttest tests to measure critical thinking skills. The results of the study show that the SSCS-based excellent service textbook was declared suitable for use based on the results of the validation of experts with the excellent category. The results of the limited trial also showed a positive response from students and an increase in critical thinking skills after using textbooks. This textbook is designed systematically by containing problem-solving-based learning activities that encourage students to actively seek information, analyze problems, develop creative solutions, and share the results of their thoughts. Thus, SSCS-based textbooks are effectively used as a learning resource that is able to integrate theory and practice and support student-centered learning and is oriented towards the development of high-level thinking skills.